An Analysis of Conjunction in Descriptive Text of English Textbook Used in Tenth Grade of Senior High School - Julian Fransiskus Xaverius Sianturi; Ayu Santiya; Elis Arianti Panjaitan; Kartina Rahmadhani Rambe (Institut Agama Islam Negeri Palopo, 2021)
The purpose of this study was to look at conjunctions in a descriptive text from a Senior High School textbook for the tenth grade. The English Textbook for Tenth Grade was employed as the research sample, and we chose SMA N 20 Medan English Textbook. This study employed two instruments: the first was a search for all the conjunction meanings, functions, and types, and the second was an analysis of the conjunctions used in the English textbook for Senior High School's Tenth Grade. The results of this study revealed that the most common types of conjunctions in English textbooks. The table shows that the Coordinating Conjunction is the most common type of conjunction in a descriptive text used in the English Textbook. The results revealed that the Coordinating Conjunctions are most prominent in the English Textbook for Senior High School's tenth grade. Which, the word “and” is most shown on the descriptive text of the English Textbook used in the tenth grade of senior high school.